Soundies and the changing image of Black Americans on screen : one dime at a time - Delson, Susan (Indiana University Press, 2021)
"In the 1940s, folks at bars and restaurants would gather around a Panoram movie machine to watch three-minute films called Soundies, precursors to today's music videos. This history was all but forgotten until the digital era brought Soundies to phones and computer screens-including a YouTube clip starring a 102-year-old Harlem dancer watching her younger self perform in Soundies. In Soundies and the Changing Image of Black Americans on Screen: One Dime at a Time, Susan Delson takes a deeper look at these fascinating films by focusing on the role of Black performers in this little-known genre. She highlights the women performers, like Dorothy Dandridge, who helped shape Soundies, while offering an intimate look at icons of the age, such as Duke Ellington and Nat King Cole. Using previously unknown archival materials-including letters, corporate memos, and courtroom testimony-to trace the precarious path of Soundies, Delson presents an incisive pop-culture snapshot of race relations during and just after World War II. Perfect for readers interested in film, American history, and Black entertainment history, Soundies and the Changing Image of Black Americans on Screen and its companion video website (susandelson.com) bring the important contributions of these Black artists into the spotlight once again"--